Na fronteira da intolerância: ecos de povos em deslocamento - Corsi, Joice Camila (2020)
We have been targeted daily by news related to the worldwide migration flow. As predicted by Foucault ([1979] 2010), excessive antagonisms within the bosom of society have mobilized the massive displacement of people. Dictatorial states, civil wars, political or religious persecution, human rights violations and even natural disasters are some of the factors that shape the “new migratory flows” (CAVALCANTI e col. (2019). Based on the understanding of Albuquerque Júnior's (2016) considerations about the practice of xenophobia and its motivations, and on the nuances between intolerance and tolerance (DUNKER, 2014), we are mainly interested in problematizing the old saying about Brazilian people’s cordiality (BUARQUE HOLANDA, 1995). In general, we aim to indicate if there are mutations in the identity traits attributed to Brazilians and specifically to analyze how the possible mutations can be apprehended in the forms of discursivization of migratory policies, whether in semantic determinations or projections of presidents' speeches. For this, we will analyze how three subjects who have already experienced or still experience the condition of Heads of State, Dilma Rousseff, Michel Temer and Jair Bolsonaro used, in public speaking circumstances, the terms employed to refer to “people on the move”. In this analysis we will observe how the identity images attributed by these three political figures to people on the move are intrinsically related to historical issues, which pass through the forms of cordiality and its absence. We chose 2015 as a starting point because of the record number of displaced people (NAÇÕES UNIDAS, 2015), the considerable increase in the interest of internet users for the terms 'refugees', 'migrants' and 'immigrants' (GOOGLE TRENDS) and also by the eruption of the historical-discursive event, which was recognized as the symbol of the migratory crisis, the death of Syrian boy Aylan Kurd (G1, 2015). To this end, we will base ourselves on Foucaultian reflections on the dynamics of the emergency conditions of utterances, discursive memory, power strategies, among other contributions of the author to undertake our reflections. Results indicate that the stereotype of the cordial man is deeply rooted in the imagination and collective memory rather than in the practices themselves. Cordiality is conditioned by the maneuvers of our leaders, the convictions of our representatives in different spheres and follows under the watchful eye of xenophobia.